A General Protein O-Glycosylation Gene Cluster Encodes the Species-Specific Glycan of the Oral Pathogen Tannerella forsythia: O-Glycan Biosynthesis and Immunological Implications - Tomek, Markus B.; Maresch, Daniel; Windwarder, Markus; Friedrich, Valentin; Janesch, Bettina; Fuchs, Kristina; Neumann, Laura; Nimeth, Irene; Zwickl, Nikolaus F.; Dohm, Juliane C.; Everest-Dass, Arun; Kolarich, Daniel; et al. (Frontiers in Microbiology, 2018)
The cell surface of the oral pathogen Tannerella forsythia is heavily glycosylated with a unique, complex decasaccharide that is O glycosidically linked to the bacterium's abundant surface (S-) layer, as well as other proteins. The S-layer glycoproteins are virulence factors of T. forsythia and there is evidence that protein O-glycosylation underpins the bacterium's pathogenicity. To elucidate the protein O-glycosylation pathway, genes suspected of encoding pathway components were first identified in the genome sequence of the ATCC 43037 type strain, revealing a 27-kb gene cluster that was shown to be polycistronic. Using a gene deletion approach targeted at predicted glycosyltransferases and methyltransferases encoded in this gene cluster, in combination with mass spectrometry of the protein-released O glycans, we show that the gene cluster encodes the species specific part of the T. forsythia ATCC 43037 decasaccharide and that this is assembled step-wise on a pentasaccharide core. The corewas previously proposed to be conserved within the Bacteroidetes phylum, to which T. forsythia is affiliated, and its biosynthesis is encoded elsewhere on the bacterial genome. Next, to assess the prevalence of protein O glycosylation among Tannerella sp., the publicly available genome sequences of six T. forsythia strains were compared, revealing gene clusters of similar size and organization as found in the ATCC 43037 type strain. The corresponding region in the genome of a periodontal health associated Tannerella isolate showed a different gene composition lacking most of the genes commonly found in the pathogenic strains. Finally, we investigated whether differential cell surface glycosylation impacts T. forsythia’s overall immunogenicity. Release of proinflammatory cytokines by dendritic cells upon stimulation with defined glycosyltransferase-deficient mutants of the type strain was measured and their T cell-priming potential post-stimulation was explored. This revealed that the O glycan is pivotal to modulating dendritic cell effector functions, with the T. forsythia-specific glycan portion suppressing and the pentasaccharide core activating a Th17 response. We conclude that complex protein O glycosylation is a hallmark of pathogenic T. forsythia strains and propose it as a valuable target for the design of novel antimicrobials against periodontitis.